(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article addresses the importance of incorporating cultural elements into Korean language education to enhance students’ linguocultural competence. Recognizing that language and culture are deeply interconnected, the study explores strategies that allow learners to achieve both linguistic proficiency and cultural insight. Key strategies discussed include the integration of culturally relevant texts, multimedia resources, and interactive activities such as role-playing and cultural exchanges, which serve as practical applications of language in real-life Korean contexts.